Collective ambiguous loss after mass hostage-taking in war: exploring public mental health outcomes and resilience - Einat Yehene; Shay Ohayon; Adi Yahav; Hagai Levine (European Journal of Psychotraumatology)
Objective: Collective ambiguous loss can arise in communities facing the unresolved absence or presence of loved ones, marked by uncertainty and confusion. This study examines the impact of such loss on the general public in Israel after 251 individuals were taken hostage by Hamas on October 7 2023.Method: A diverse sample of 740 participants (ages 18–85, 58.2% women) took part in a comprehensive survey from December 2023 to January 2024. The survey measured boundary ambiguity (BA), separation distress related to disappearance (Ambiguous Loss Inventory Plus – ALI + - SD), general psychological distress (Mini-DASS), and personal resilience factors: ambiguity tolerance (Need for Closure Scale-Revised, NCSR) and psychological flexibility (PF).Results: Public stances indicated that 85% of respondents had moderate to very low confidence in the hostages’ return, coupled with high endorsement of psychological engagement indicators such as emotional pain, intrusive thoughts, and survivor guilt. Those acquainted with a hostage (12%) showed no differences in stances or ALI + -SD and Mini-DASS levels, except for higher BA and greater engagement in demonstrations activities for their return. SEM analysis showed that ALI + -SD mediated the relationship between BA and Mini-DASS (high BA related to high general distress). In this model, BA and ALI + -SD explained over half of the variation in general psychological distress (R2 = 53%). A second model revealed serial mediation by BA and ALI + -SD in the relationship between NCSR and Mini-DASS, with lower ambiguity tolerance related to increased general distress. However, no such mediation was observed in the relationship between PF and Mini-DASS, and overall, the effect of personal resilience on general distress was relatively small.Conclusions: Mass hostage-taking substantially impacts society’s mental health, extending beyond personal acquaintance with a hostage. The findings underscore the need to shift focus from personal resilience to community-based policies and therapeutic approaches to effectively address communal ambiguous loss amid collective trauma.